Surgical treatment of complete ventricular atrium block. Placement of pacemaker for permanent stimulation: about 3 observations - Rubio, Roberto; Sanjinés, Aníbal; Abó, Juan C; Peña, L (Cirugía del Uruguay, 2020)
Presented at session 7th November 1962